Investigating the functional relationship between streptokinase variants from Group A Streptococcus, and associated M-like proteins. Issue 7 (10th July 2020) - Cherrington, Sophie; Maqbool, Azhar; Philippou, Helen; Thelwell, Craig
Abstract : Background: Streptokinase (SK) from Group A streptococcus (GAS) activates human plasminogen to generate plasmin, which degrades fibrin clots tofacilitate bacterial dissemination. Sequence variants of SK from diverse GAS strains form distinct evolutionary clusters.Unlike cluster 1 SK, cluster 2 variants have very little activity in solution and depend on co-factors (e.g. fibrin(ogen)).Cluster 2 SK variants also appear to correlate with cell-surface M-like proteins: SK2a with M1 (fibrinogen-binding) and SK2b with PAM (plasminogen-binding). Methods: Plasminogen activation by recombinant SKs (rSK2a, rSK2b) was investigated by chromogenic assay; nickel-coated microtiter plates were used to immobilise recombinant M proteins (rPAM and rM1) via a C–terminal His tag to mimic cell surface plasmin generation. Results: Plasminogen activation by rSK2b is stimulated ∼18-fold by rPAM in solution; when rPAM is immobilised stimulation exceeds 100-fold. Fibrin is the most potent stimulator of rSK2a activity (7-fold increase) compared to fibrinogen (4-fold); when rM1 was included, either in solution or immobilised, there was no further stimulation of rSK2a activity with fibrinogen. Discussion: Stimulation ofSK2b activity by plasminogen bound to immobilised PAM suggests an important role for cell-surface plasmin generation. SK2a activity appears to be independent of M1, targeting fibrin directly. SK variants are commonly associated with distinct disease manifestations with SK2b commonly expressed by invasive skin-tropic strains of GAS and SK2a by nasopharynx-tropic strains. An improved understanding of the molecular mechanism of action by GAS SK variants may help to identify potential novel therapeutic targets for the treatment of invasive GAS diseases.